Locate The Circumcircle

Geometry Level 4

Triangle A B C ABC is located in the x y xy -plane with circumcenter I I and centroid G ( 8 3 ; 0 ) G(\frac{8}{3};0) . Points M ( 0 ; 1 ) M(0;1) and N ( 4 ; 1 ) N(4;1) are the reflections of point I I across the lines A B AB and A C AC respectively.

Assuming that line B C BC contains point ( 2 ; 1 ) (2;-1) . Locate the circumcircle of triangle A B C ABC by finding its center I ( a ; b ) I(a;b) and its radius c \sqrt{c} . Submit your answer as the integer a b c \overline{abc} .


The answer is 305.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Aug 10, 2019

Let a = I A \mathbf{a} = \overrightarrow{IA} , b = I B \mathbf{b} = \overrightarrow{IB} , c = I C \mathbf{c} = \overrightarrow{IC} , q = O I \mathbf{q} = \overrightarrow{OI} . Then a = b = c = R |\mathbf{a}| = |\mathbf{b}| = |\mathbf{c}| = R , the outradius.

Then a + b \mathbf{a}+\mathbf{b} is a vector perpendicular to A B \overrightarrow{AB} , and it follows that I M = a + b \overrightarrow{IM} = \mathbf{a}+\mathbf{b} . Similarly I N = a + c \overrightarrow{IN} = \mathbf{a}+\mathbf{c} . In addition 1 3 ( a + b + c ) = I G \tfrac13(\mathbf{a}+\mathbf{b} + \mathbf{c}) = \overrightarrow{IG} . Thus a + b = ( 0 1 ) q a + c = ( 4 1 ) q a + b + c = ( 8 0 ) 3 q \begin{aligned} \mathbf{a} + \mathbf{b} & = \; \binom{0}{1} - \mathbf{q} \\ \mathbf{a} + \mathbf{c} & = \; \binom{4}{1} - \mathbf{q} \\ \mathbf{a} + \mathbf{b} + \mathbf{c} & = \; \binom{8}{0} - 3\mathbf{q} \end{aligned} and hence a = ( 4 2 ) + q b = ( 4 1 ) 2 q a = ( 8 1 ) 2 q \mathbf{a} \; = \; \binom{-4}{2} + \mathbf{q} \hspace{1cm}\mathbf{b} \; = \; \binom{4}{-1} - 2\mathbf{q} \hspace{1cm}\mathbf{a} \; = \; \binom{8}{-1} - 2\mathbf{q} Since ( 2 , 1 ) (2,-1) lies on B C BC , we deduce that ( 2 1 ) q = λ b + ( 1 λ ) c = ( 8 4 λ 1 ) 2 q \binom{2}{-1} - \mathbf{q} \; = \; \lambda\mathbf{b} + (1-\lambda)\mathbf{c} \; = \; \binom{8-4\lambda}{-1} - 2\mathbf{q} for some λ \lambda , and hence that q = ( α 0 ) \mathbf{q} = \binom{\alpha}{0} for some α \alpha . Since a , b , c \mathbf{a},\mathbf{b},\mathbf{c} must all have the same length (the outradius), we deduce that α = 3 \alpha = 3 .

Thus we deduce the coordinates A ( 2 , 2 ) A\;(2,2) , B ( 1 , 1 ) B\;(1,-1) , C ( 5 , 1 ) C\;(5,-1) and I ( 3 , 0 ) I\;(3,-0) , with outradius 5 \sqrt{5} . Thus the answer is 305 \boxed{305} .

Leah Jurgens
Aug 10, 2019

Note: The above graph is now drawn to scale.

The equation of line B C BC which contains point ( 2 ; 1 ) (2;-1) and is parallel to line M N MN is y = 1 y=-1 .

Let point H H and E E be the midpoints of M N MN and B C BC respectively.

H H has the coordinate of ( 2 ; 1 ) (2;1) .

We can easily prove that A H E I AHEI is a parallelogram.

Let F F be the midpoint of I E IE .

Because A G = 2 G E AG=2GE , combined with A H E I AHEI being a parallelogram, we can deduce that H G = 2 G F HG=2GF .

Using H G = 2 G F HG=2GF with coordinates of points H H and G G being known, we can find the coordinate of point F F .

We can find the the equation of line E F EF which contains point F F and is perpendicular to line B C BC .

Then find the coordinate of point E E which is the intersection of lines E F EF and B C BC .

Using the equation I F = F E IF=FE , we can find the coordinate of point I I as ( 3 ; 0 ) (3;0) and I A = H E = 5 IA=HE=\sqrt{5} which is also the radius.

In conclusion, we can submit the answer as 305 \boxed{\overline{305}} .

Ajit Athle
Aug 11, 2019

Let A:(x1,y1), B:(x2,y2) & C:(x3,y3). Then x1+x2=a, y1+y2=b+1, x1+x3=a+4, y1+y3=b+1, x1+x2+x3=8, y1+y2+y3=0 These equations, yield A:[(2a-4),(2b+2)], B:[(4-a),(-b-1)] and C:[(8-a),(-b-1)]. Since I:(a,b) is the circum-centre with radius = √c, we can further write the following equations: ((2a-4)-a)^2+((2b+2)-b)^2=c -----(1) ((4-a)-a)^2+((-b-1)-b)^2=c --------(2) and ((8-a)-a)^2+((-b-1)-b)^2=c --------(3) **These yield, a=3, b=0 & c=5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...